Hier und Anderswo. Palästina-Israel im essayistischen Film (1960-2010) - Grabher, Peter (2020)
Peter Grabher questions how French, Israeli and Palestinian filmmakers between 1960 and 2010 have dealt with the Middle East conflict and with audiovisual representations concerning Israel-Palestine. He examines the transgressive strategies of essay films by Chris Marker, Jean-Luc Godard/Anne-Marie Miéville, Ariella Azoulay, Udi Aloni, Ula Tabari und Elia Suleiman and provides a detailed analysis of their historical and aesthetic context.